STUDENTS’ MOTIVATION TO SPEAK IN A GROUP DISCUSSION - Maulana, Fajar; Ikhsanudin, Ikhsanudin; Suhartono, Luwandi (FKIP - Universitas Tanjungpura, 2020)
This research was done to know the factors’ influencing students’ motivation to speak in a group discussion. This research is qualitative survey, in which the subjects are the Third-Semester Students of English Education Study Program of Tanjungpura University in Academic Year 2018/2019. The subjects of this research were 25 students in class A. The data were collected through observation and survey. Based on the data the students are motivated enough in speaking class and the motivation are relatively high across the students but most of the students faced several speaking problems such as afraid of making mistakes, lack of confidence, and lack of motivation. In summary, the factors that influenced the students’ motivation to speak in a group discussion are the students' interest to the materials of learning, the students’ interest to the culture of the target language, and lastly the reinforced that the students receive inside/outside the teaching and learning process. All of the factors are related to types of motivation, such as, intrinsic, extrinsic, instrumental, and integrative motivation. The writer claimed that knowing and understand sorts of motivation is essential with the intention of making a better teaching and learning environment